Acceptance Measurement of Health Insurance Information System Based on Technology Acceptance Model - Nurhayati, Siti; Hidayat, Nurul (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
The objective of this research is to evaluate P-Care BPJS information system based on Technology Acceptance Model (TAM). The type of research is analytical, cross sectional approach. Number of respondents 206 P-Care BPJS users at primary health care. Data analysis using linear regression. Based on correlation test external variables with percieved usefulness, showed high correlation = 0.6 (p <0.001); external variables with percieved ease of use showed moderate correlation = 0.4 (p <0.001); perceived ease of use with attitude showed moderate correlation = 0.5 (p <0.001); percieved usefulness with attitude showed high correlation = 0.7 (p <0.001); perceived usefulness with actual use showed moderate correlation = 0.5 (p <0.001); behavioral intention to use with percieved usefulness showed moderate correlation = 0.5 (p <0.001); attitude with behavioral intention to use showed high correlation = 0.6 (p <0.001); behavioral intention to use with actual use showed high correlation = 0.7 (p <0.001).